1981
DOI: 10.1063/1.329011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fracture and spallation in ductile solids

Abstract: A mathematical model of ductile hole growth under the application of a mean tensile stress is developed and applied to the problem of spallation in solids. The object is to describe dynamic ductile fracture under a wide range of tensile loading conditions. The mathematical model presented here describes both plate-impact spallation (as observed by postshot examination and time-resolved pressure measurements) and explosively produced spallation (as observed by dynamic x-radiographic techniques) in copper. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(169 citation statements)
references
References 25 publications
2
160
0
4
Order By: Relevance
“…It should be noted that the contributing factors for materials spalling have been studied for decades [21][22][23][24][25][26][27] and the phenomenon of spall was documented by Hopkinson [28]. Nevertheless, unlike FCC and BCC metals where the shock response has been reviewed [29,30], no such review exists for HCP metals.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the contributing factors for materials spalling have been studied for decades [21][22][23][24][25][26][27] and the phenomenon of spall was documented by Hopkinson [28]. Nevertheless, unlike FCC and BCC metals where the shock response has been reviewed [29,30], no such review exists for HCP metals.…”
Section: Introductionmentioning
confidence: 99%
“…The second term I;,(a)& denotes the influence of the material viscosity, which describes the effect of the rate sensitivity and is one of the major features differing from the quasi-static growth of voids. Other researchers' studies, such as Curran et al (1987), Johnson (1981) and Cortes (1992), have resulted in the same fact. The third term F,(a) is the total effects of the applied external stress, the change of the void surface energy, work-hardening and the yield stress in the solid surrounding the void on the void growth.…”
Section: (24)mentioning
confidence: 76%
“…Johnson (1981) once numerically analyzed the change of temperature at expanding pore wall for copper-like material, and showed that if all the plastic work went into heat, the temperature at the expanding pore wall could be a substantial fraction of the melting temperature. Cortes (1992) investigated the thermal softening of the matrix material.…”
Section: +I-psementioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Subsequent void growth has also been extensively investigated over the past several decades, and substantial micromechanical models have been proposed for understanding the quasi-static void growth 44,52,53 or the dynamic void growth under extreme loading conditions. 39,[54][55][56][57][58][59][60][61][62] Moreover, a few modeling papers have suggested that the porosity achieved at the peak tensile stress is typically low (<1%), and the void coalescence is achieved long after the peak tensile stress. [63][64][65] Thus, it was proposed that the void coalescence behavior has no perceivable influence on the pull-back velocity and spall strength.…”
Section: Effect Of the Microstructure On The Shock And Spall Behaviormentioning
confidence: 99%